Invasão celular e infecção oral por cepas de Trypanosoma cruzi dos grupos genéticos TcI e TcIV isoladas de portadores da doença de Chagas - Maeda, Fernando Yukio [UNIFESP] (2016)
Outbreaks of acute Chagas disease by oral infection have been reported frequently over the last 10 years, with higher incidence in northern South America, where predominates the Trypanosoma cruzi lineage TcI, responsible for the major cause of resurgent human disease, and a small percentage is identified as TcIV. Mechanisms of oral infection and host cell invasion by metacyclic trypomastigotes of these groups of parasites are poorly understood. To address that question, we analyzed T. cruzi strains isolated from patients with Chagas disease from Venezuela, Guatemala and Brazil, by giving metacyclic trypomastigotes forms by oral route in mice. All parasite strains were poorly infective. Parasites were either undetectable or were detected in small numbers in the mouse stomach 4 days post-infection. At day 30, amastigote nests were found in the stomach and/or in the heart. As compared to TcI lineage, the capacity of TcIV parasites to traverse the gastric mucin-coated transwell filter was higher. Cell invasion assays revealed a reduced capacity of all parasites in invading human epithelial cells. Expression of gp82, the surface molecule that mediates cell invasion and is resistant to digestion by pepsin, was similar in all strains. As regards gp90, the surface molecule that negatively regulates invasion and is also resistant to peptic degradation, the expression was higher in TcI parasites. Gp90, which was released into medium by TcI and TcIV parasites, inhibited cell invasion. Our findings have indicated that TcI lineage has low capacity in relation to lineage TcIV, in invading e the gastric epithelium after oral infection in mice, what may can be associated with the capacity of metacyclic trypomastigotes, in particular TcI parasites, in migrating through the mucus layer and to invade the target cells.